Odor assessment tools and odor emissions in industrial processes - doi: 10.4025/actascitechnol.v32i3.4778 (Acta Scientiarum. Technology, 2010)
Environmental odors are an inherent part of any given process and can frequently be a cause of public environmental discomfort. Brazilian regulations are now characterizing odors as a form of air pollution and state that odor discomfort on surrounding populations must be avoided by industries. No olfactometry-related technology is standardized or even recognized. This makes it vital to create a federal reference, at least methodological, on the subject. Thus, the present work had the objective to apply, adjust, and evaluate the results of different olfactometric techniques in three types of industries which are known as odorous. The points of most significant odor emission to wastewater treatment plants were located at the system inputs. The techniques that were used are based on international standards and regulations. In all case studies, the applied odor assessment methods (odor intensity, quality, hedonic character and concentration) were found to be satisfactory for representing the odor situation. The method presented in this paper for evaluating the hedonic tone proved to be very convenient. These methodologies allowed for the results to be presented in a numerical form, providing with objective results from subjective analyses.